EFEKTIVITAS MEDIA VIDEO PEMBELAJARAN DALAM PENGUATAN PEMBIASAAN MAKAN SEHAT BERGIZI PADA SISWA KELAS IV SD NEGERI 3 BUNUTIN - Ni Komang Yuspitayani; Nurul Isnaini Fitriyana; Ni Wayan Sri Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the frequency of using instructional video media, describe the reinforcement of healthy eating habits, and analyze the effectiveness of instructional videos for fourth-grade students at SD Negeri 3 Bunutin. This research employed a descriptive qualitative approach involving fourth-grade teachers and students as participants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings showed that instructional videos were used regularly according to lessons on healthy and nutritious foods. The reinforcement of healthy eating habits was carried out through instructional videos, classroom discussions, teacher guidance, supervision, and encouraging students to bring healthy lunches to school. The use of instructional videos effectively increased students' attention, enthusiasm, and understanding of healthy eating, promoted active participation during learning, and encouraged students to adopt healthier food choices in their daily lives. Therefore, instructional video media are effective in strengthening healthy eating habits among fourth-grade students at SD Negeri 3 Bunutin.